A Telomerase-Derived Peptide Exerts an Anti-Hepatitis B Virus Effect via Mitochondrial DNA Stress-Dependent Type I Interferon Production - Choi, Yu-Min; Kim, Hong; Lee, Seoung-Ae; Lee, So-Young; Kim, Bum-Joon (Frontiers in Immunology, 2020)
Previously, a telomerase-derived 16-mer peptide, GV1001, developed as an anti-cancer vaccine, was reported to exert antiviral effects on human immunodeficiency virus or hepatitis C virus in a heat shock protein-dependent manner. Here, we investigated whether GV1001 exerts antiviral effects on hepatitis B virus and elucidated its underlying mechanisms. GV1001 inhibited HBV replication and HBsAg secretion in a dose-dependent manner, showing synergistic antiviral effects with nucleos(t)ide analogs (NAs) including entecavir (ETV) and lamivudine (LMV). This peptide also inhibited viral cccDNA and pgRNA. Intravenous GV1001 treatment of transgenic mice had anti-HBV effects. Our mechanistic studies revealed that GV1001 suppresses HBV replication by inhibiting capsid formation via Type I interferon-mediated induction of heme oxygenase-1. GV1001 promoted mitochondrial DNA stress-mediated release of oxidized DNA into the cytosol, resulting in IFN-I-dependent anti-HBV effects via the STING-IRF3 axis. We found that the anti-HBV effect of GV1001 was due to its ability to penetrate into the cytosol via extracellular heat shock protein, leading to phagosomal escape-mediated mtDNA stress. We demonstrated that the cell-penetrating and cytosolic localization capacity of GV1001 results in antiviral effects on HBV infections via mtDNA stress-mediated IFN-I production. Thus, GV1001, a peptide proven to be safe for human use, may be an anti-HBV drug that, can be synergistically used with nucleot(s)ide analogue.